2021
DOI: 10.1093/cid/ciab1059
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate Use of REGEN-COV® in Patients With Coronavirus Disease 2019 (COVID-19) and Immunodeficiency-Associated Antibody Disorders

Abstract: Background Patients with immunodeficiency-associated antibody disorders are at a higher risk of prolonged/persistent COVID-19 infection, having no viable treatment options. Methods A retrospective analysis of patients with primary and/or secondary immunodeficiency-associated antibody disorders who received casirivimab and imdevimab (REGEN-COV ®) under emergency compassionate use. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Supportive evidence of CAS + IMD efficacy in patients with B-cell deficiency and dysfunction was previously reported. 26 Additionally, regarding the seroconversion data presented in this analysis, we recognise that anti-nucleocapsid IgG response wanes, and that some participants who were infected might not have developed an antibody response. To compensate, we collected serology samples at multiple timepoints during the study to capture even a transient anti-nucleocapsid IgG response.…”
Section: Discussionmentioning
confidence: 92%
“…Supportive evidence of CAS + IMD efficacy in patients with B-cell deficiency and dysfunction was previously reported. 26 Additionally, regarding the seroconversion data presented in this analysis, we recognise that anti-nucleocapsid IgG response wanes, and that some participants who were infected might not have developed an antibody response. To compensate, we collected serology samples at multiple timepoints during the study to capture even a transient anti-nucleocapsid IgG response.…”
Section: Discussionmentioning
confidence: 92%
“…To the Editor —In their recent article, Stein et al reported efficiency of REGN-CoV-2 ® in patients with long-standing coronavirus disease 2019 (COVID-19), allowing rapid viral clearance and clinical improvement [ 1 ]. This therapy, using monoclonal antibodies (mAbs) targeting the receptor-binding domain of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein, is also currently used for active immunization of COVID-19 in immunocompromised patients that do not respond to a complete vaccine schedule.…”
mentioning
confidence: 99%
“…As far as we are aware, only few data are available regarding the same treatments in patients with secondary immunodeficiencies, mainly focusing on severe COVID-19 and hospitalized patients. In the available studies, SARS-CoV-2 specific treatments were often late administered during the disease course ( 51 , 53 ). Moreover, available series and studies generally group patients according to the cause of secondary immunodeficiencies (e.g.…”
Section: Discussionmentioning
confidence: 99%